AN ANALYSIS OF ENGLISH TEACHERS’ BASIC TEACHING SKILLS AT SMP NEGERI 8 BUTON REGENCY - Mido, La (English Education Journal, 2024)
The objective of this research was to analyse the English teacher basic teaching skill at SMP Negeri 8 Buton regency. The significance of the research were provide information and additional insight within basic teaching skills and how they are applied in teaching English, give additional knowledge and experience in the implementation of teaching skills in teaching. The subject was the English teacher who have good basic teaching skills in teaching so get it the researcher selected senior English teacher at SMP Negeri 8 Buton regency. This research applied a qualitative research. so human instrument as the key instrument. It means that the researcher himself as the key instrument in this research. In colecting the data, the researcher applied the observation and interview. Participant observation and semi-structure interview were used in collecting the data about teaching skills of English teacher. The data kualitatif analysed by using data reduction, data display and drawing conclusions or verification. The result of the research showed that there were two basic teaching skills observed and interviewd that were opening the lesson and closing the lesson. In opening the lesson, skills were observed and interviewed were skills on attract the studdents’ attention, enhance the students’ motivation, Provide a reference in starting learning activities and skills on creating links between activities. Meanwhile in closing the lesson the skills were observed and interviewed were skills on reviewing the learning that has been done, skills on learning Evaluation and skills on providing students’ psychological or social encouragement.